O05 Flow diversion for recurrent aneurysms after stent-assisted coiling: multicenter experience. (29th August 2022) - Salem, M; Fargen, K; Lanzino, G; Tanweer, O; Spiotta, A; Shapiro, M; Tjoumakaris, SI; Kim, L; Levitt, MR; Kan, P; Hassan, A; Ducruet, A; et al.
Abstract : Introduction: There is limited data regarding the safety and efficacy of salvage flow diversion (FD) in persistent/recanalized aneurysms after stent-assisted coiling (SAC), which can occur in 15–20% of cases, with preliminary data suggesting lower efficacy in this particular subgroup. Aim of study: To study FD after SAC in a large multicenter cohort. Methods: A series of consecutive patients undergoing FD after SAC from 16 institutions were included (2011–2021) were included, with a primary outcome of angiographic occlusion and secondary outcomes of safety and complications. Results: Eighty-two patients (median-age 57, 69.5% females) were included. The majority of aneurysms were located in the internal carotid artery (70.7%%), saccular in morphology (81.7%), with a median maximal diameter of 9 mm (IQR 5.6–15), and 51.2% initially presenting as ruptured aneurysms. The median elapsed time between initial SAC and salvage FD was 25.1 months, with Pipeline Embolization Device (PED) being the most commonly utilized FD device (95.1%). At a median follow-up of 19 months after FD, complete angiographic occlusion was achieved in 64.7% of cases, and near-complete occlusion (90–99%) in 17.6% of the cases. Permanent thromboembolic complications were encountered in 2.4% of the patients, and one procedural mortality secondary to hemorrhagic complication (1.2%). Favorable modified Rankin Scale (mRS) of 0–2 was encountered in 94.4% of patients on last available clinical follow-up. Conclusions: Flow diversion for recurrent aneurysms after SAC is associated with a reasonable safety and efficacy profiles, comparable to de-novo flow-diverted aneurysms. Do you have any conflict of interest to declare? : No